US Drug Overdose Mortality: 2009–2018 Increases Affect Young People Who Use Drugs - Gaur, Dhruv S. (Int J Drug Policy, 2020)
PURPOSE: Drug overdose mortality remains a public health concern in many countries globally. In the US, overdoses involving synthetic opioids are the primary contributor to overdose mortality. We aimed to assess trends in overdose death due to synthetic opioids among young people and describe key demographic and temporal changes. METHODS: Data from the US National Vital Statistics System Multiple Cause of Death files for 2009–2018 were analysed to determine age-specific overdose death rates by region (i.e. east versus west of the Mississippi River). Age-adjusted overdose mortality rates were used to compare demographic differences in all drug and synthetic opioid overdose among young people (aged 15–34 years) using a joinpoint regression with Poisson-approximated standard errors. RESULTS: Driven by synthetic opioid overdose, the age burden of mortality shifted towards young people in eastern states and remained approximately constant in western states over the study period. The highest increases in drug overdose mortality rates were observed in young Black and Hispanic people and those living in large metropolitan areas. CONCLUSIONS: Rapid changes in the demographics of overdose demonstrate distinct but overlapping US overdose sub-epidemics, and highlight the need for targeted interventions to reduce overdose risk in young people.